Caught in a Flood of Negative Information: Doomscrolling and Fear of Missing Out (FoMO) as Predictors of Negative Affect in Generation Z - Salfatya Santoso; Abdullah Azzam Al Afghani (Universitas Katolik Soegijapranata, 2026)
Generation Z’s heavy use of social media increases their exposure to negative information, which can lead to psychological effects such as negative affect, unpleasant emotional experiences like anger, fear, anxiety, and low self-esteem. This condition is linked to the phenomenon of doomscrolling, the habit of continuously scrolling through negative content, as well as Fear of Missing Out (FoMO), the feeling of anxiety about being left out of others’ information or social experiences. This research aims to analyze the extent to which doomscrolling and FoMO predict negative affect among Generation Z social media users. This research employs a quantitative approach using purposive sampling on 150 Generation Z individuals who are active social media users. The instruments used include the Doomscrolling Scale, the Online Fear of Missing Out (ON-FoMO) Scale, and the Negative Affect Scale. Data were analyzed using multiple linear regression. The results indicate that doomscrolling and FoMO are simultaneously positive and significant predictors of negative affect, with an effective contribution of 19.5%. These findings suggest that repetitive negative information and digital social anxiety can increase negative affect among Generation Z.